2013
DOI: 10.1098/rspb.2013.0503
|View full text |Cite
|
Sign up to set email alerts
|

Sex allocation pattern of the diatomCyclotella meneghiniana

Abstract: Sex allocation is one of the most successful applications of evolutionary game theory. This theory has usually been applied to multicellular organisms; however, conditional sex allocation in unicellular organisms remains an unexplored field of research. Observations at the cellular level are indispensable for an understanding of the phenotypic sex allocation strategy among individuals within clonal unicellular organisms. The diatom Cyclotella meneghiniana, in which the sexes are generated from vegetative cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Oogonia, auxospores, and spermatogonia in the other species studied displayed similar morphologies to those observed in T . pseudonana and other centric diatoms ( Fig 3L–3O , S2M–S2P Fig , Fig 4A ) [ 11 , 16 , 28 , 33 , 35 , 37 , 38 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Oogonia, auxospores, and spermatogonia in the other species studied displayed similar morphologies to those observed in T . pseudonana and other centric diatoms ( Fig 3L–3O , S2M–S2P Fig , Fig 4A ) [ 11 , 16 , 28 , 33 , 35 , 37 , 38 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…that reported sex allocation of each mother cell using a microdevice in C. meneghiniana [28]. In this study, we revealed the evolutionary basis and proximate factors that contribute to adjusting the male emergence timing using the experimental system [28].…”
Section: Introductionmentioning
confidence: 79%
“…In estuaries, the predominance and large outbreaks of C. meneghiniana are often reported [21][22][23], and the induction of sexual reproduction has been suggested [24,25]. Moreover, saline conditions in the laboratory usually induce a male-biased sex ratio in this species [26][27][28]; thus, numerous sperm have been observed to surround a single egg during the mating process [19]. These results suggest that C. meneghiniana could potentially experience sperm competition in nature induced by male-biased sexual differentiation at high cell density.…”
Section: Introductionmentioning
confidence: 99%
“…One adaptation widely used by diatoms is a size reduction and size restitution cycle to time the length of their life cycle, which enables them to switch cell resources from asexual cell division to sexual reproduction under optimum conditions (see Drebes 1977 ;Lewis 1983Lewis , 1984Jewson 1992 ;Edlund and Stoermer 1997 ;Chepurnov et al 2004 ;Mann 2011 ;Shirokawa and Shimada 2013 ;Kaczmarska et al 2013 ). The importance of the role of sexual reproduction in population dynamics in marine planktonic diatoms is becoming recognized (e.g., Crawford 1995 ;D'Alelio et al 2010 ).…”
Section: Life Historymentioning
confidence: 97%